Cappuccino, a Drosophila maternal effect gene required for polarity of the egg and embryo, is related to the vertebrate limb deformity locus. - Emmons, S.; Phan, H.; Calley, J.; Chen, W.; James, B.; Manseau, L. (Genes & Development, 1995)
We report the molecular isolation of cappuccino (capu), a gene required for localization of molecular determinants within the developing Drosophila oocyte. The carboxy-terminal half of the capu protein is closely related to that of the vertebrate limb deformity locus, which is known to function in polarity determination in the developing vertebrate limb. In addition, capu shares both a proline-rich region and a 70-amino-acid domain with a number of other genes, two of which also function in pattern formation, the Saccharomyes cerevisiae BNI1 gene and the Aspergillus FigA gene. We also show that capu mutant oocytes have abnormal microtubule distributions and premature microtubule-based cytoplasmic streaming within the oocyte, but that neither the speed nor the timing of the cytoplasmic streaming correlates with the strength of the mutant allele. This suggests that the premature cytoplasmic streaming in capu mutant oocytes does not suffice to explain the patterning defects. By inducing cytoplasmic streaming in wild-type oocytes during mid-oogenesis, we show that premature cytoplasmic streaming can displace staufen protein from the posterior pole, but not gurken mRNA from around the oocyte nucleus.